Potential Disputes in Government Bank Building Construction Projects in Indonesia - Arjon, Arjon; Hardjomuljadi, Sarwono (ASTONJADRO, 2024)
Study This aim For know potency project disputes construction building government bank building in Indonesia. In study This done review systematic library done especially formerly in accordance with specified guidelines. inspection with reading and skimming is done sequentially to identify relevant publications. Analysis References done based on analysis content thematic, for implementation study This method used is correlation regression (research quantitative with questionnaire). Research results This state that inadequate planning and design ripe own very big influence lateness settlement upcoming project cause dispute project and quality poor/deficient work experienced influential big in discrepancy quality upcoming project cause dispute project. Also a factor external related change price and scarcity material raw own influence big reason happening dispute project.